Hydrological Evolution of a Lake Recharged by Groundwater in the Badain Jaran Desert Over the Past 140 years - Jiang, Gaolei; Wang, Nai’ang; Mao, Xin; Zhao, Hua; Liu, Linjing; Shen, Jianmei; Nie, Zhenlong; Wang, Zhe (Frontiers in Earth Science, 2021)
Understanding the evolution of lakes in arid areas is very important for water resource management. Previous studies have mainly focused on lakes with runoff recharge, while the evolution of groundwater recharge lakes in hyper-arid areas is still less known. In this study, an 86 cm-long sediment core was extracted from Sayinwusu Lake, recharged by groundwater in the southeastern Badain Jaran Desert, Northwest China. 210Pb and 137Cs dating, TOC and TN contents, and mineral content analysis were used to reconstruct the lake evolution over the past 140 years. The evolution of Sayinwusu Lake since 1880 can be divided into two periods. In the first period from 1880-1950, the low contents of TOC and TN and all detrital minerals in the mineral composition indicate that the lake primary productivity and salinity were low. During the second period from 1950 to 2018, TOC, TN and carbonate minerals increased rapidly at the beginning of the 1950s, indicating that lake primary productivity and salinity increased. Comprehensive analysis of regional climate data suggests that the evaporation increase caused by rising temperature is an important factor affecting lake evolution in the desert. Although precipitation has increased in the arid region of Northwest China in recent decades with increasing temperature, the enhancement of the evaporation effect is much greater. As a record from groundwater recharge lakes in deserts, our study provides new insight into projecting future lake changes in hyper-arid areas.